Comments on Hynes et al. Prevalence of Marijuana Use among University Students in Bolivia, Colombia, Ecuador and Peru. - Martinez Novack, Maria Claudia (2015)
We have read and analyzed the article entitled “Prevalence of marijuana use among university students in Bolivia, Colombia, Ecuador and Peru”. We propose some objective points which could enhance the internal validity of the study (i.e., we suggest to report participation proportions).